Chondrocyte Behavior on Micropatterns Fabricated Using Layer-by-Layer Lift-Off: Morphological Analysis. (28th May 2013) - Shaik, Jameel; Shaikh Mohammed, Javeed; McShane, Michael J.; Mills, David K.
Abstract : Cell patterning has emerged as an elegant tool in developing cellular arrays, bioreactors, biosensors, and lab-on-chip devices and for use in engineering neotissue for repair or regeneration. In this study, micropatterned surfaces were created using the layer-by-layer lift-off (LbL-LO) method for analyzing canine chondrocytes response to patterned substrates. Five materials were chosen based on our previous studies. These included: poly(dimethyldiallylammonium chloride) (PDDA), poly(ethyleneimine) (PEI), poly(styrene sulfonate) (PSS), collagen, and chondroitin sulfate (CS). The substrates were patterned with these five different materials, in five and ten bilayers, resulting in the following multilayer nanofilm architectures: (PSS/PDDA)5, (PSS/PDDA)10 ; (CS/PEI)4 /CS, (CS/PEI)9 /CS; (PSS/PEI)5, (PSS/PEI)10 ; (PSS/Collagen)5, (PSS/Collagen)10 ; (PSS/PEI)4 /PSS, (PSS/PEI)9 /PSS. Cell characterization studies were used to assess the viability, longevity, and cellular response to the configured patterned multilayer architectures. The cumulative cell characterization data suggests that cell viability, longevity, and functionality were enhanced on micropatterned PEI, PSS, collagen, and CS multilayer nanofilms suggesting their possible use in biomedical applications.